Degradation of organic chemicals in aqueous system through ferrate-based processes: A review. Issue 6 (December 2022) - He, Tianci; Zhou, Beihai; Chen, Huilun; Yuan, Rongfang
Abstract: Ferrate [Fe(VI)] has been proven to be an effective oxidant in wastewater treatment, and Fe(VI)-based processes have been developed in refractory pollutants treatment. In this paper, studies on refractory pollutant removal from water by Fe(VI) were systematically reviewed, along with the oxidation mechanism and influencing factors. Through self-decomposition, Fe(VI) forms high-activity Fe(V)/Fe(IV) to selectively degrade electron rich pollutants, with less limitation by the environment matrix. In particular, the oxidation of pollutants by Fe(VI) could be promoted by bicarbonate and metal ions to a certain extent. The activation methods of Fe(VI) were then summarized, including the main active substances, enhancement mechanism, and application. The free radicals produced by activation (sulfate radical, hydroxyl radical, and superoxide radical) could enhance some pollutants that were difficult to be degraded by Fe(VI) alone. Besides, the instability and storage problems of Fe(VI) limit its application in practical water treatment. The wall materials and synthesis methods of sustained-release Fe(VI) materials were discussed. However, the current discussions about environmental impacts and pollutant types remain insufficient. Future research should focus on the improvement in the optimization of Fe(VI) activation strategy for different types of pollutants and environmental risks of residual activators in water and provide guidance for the refractory pollutant removal in industry. Graphical Abstract: ga1 Highlights: The advantages of Fe(VI) were summarized. Active species and degradation mechanism of Fe(VI) activation were introduced. The recent advance in Fe(VI)-based processes was analyzed and summarized. Research needs for the development of Fe(VI)-based processes were proposed.